Body, Space, and Ritual: An Ethnography of Vipassana Meditation in Argentina - Mesa Sánchez, Daniela (2025)
This article offers an ethnographic analysis of the practice of vipassana meditation in Argentina, framed within the tradition of theravada buddhism. The research is based on fieldwork carried out at the Dhamma Sukhada meditation center, located in the town of Brandsen, Buenos Aires Province, branch of the international buddhist organization Vipassana Meditation, founded by the Burmese teacher Satya Narayan Goenka (1924–2013). Through participant observation during a ten-day silent retreat, the study examines the ritual, performative, and experiential elements that shape this practice. The article also analyzes contemporary transformations in religiosity, subjectivity, and ritual in non-Asian contexts, within the global expansion of vipassana meditation. It concludes that the retreat experience generates specific forms of subjectivation, situated at the crossroads of non-hegemonic religiosities, contemporary spiritualities, and multiple modernities.